Lowest threshold solar-pumped Ce:Nd:YAG laser with 2.06% solar-to-TEM00 mode laser conversion efficiency - Liang, Dawei (2024)
Financial support of the strategic project (UIDB/00068/2020) of the Science and Technology Foundation of the Portuguese Ministry of Science, Technology and Higher Education (FCT – MCTES) is acknowledged. Financial support by the Solar Facilities for European Research Area – Third Phase (SFERA III), Grant Agreement No. 823802 is gratefully acknowledged. The FCT-MCTES fellowship grants PD/BD/ 142827/2018, SFRH/BPD/125116/2016, SFRH/BD/145322/2019, 2021.06172.BD of D. Garcia, C. R. Vistas, M. Catela, H. Costa, respectively, and the Contract CEECIND/03081/2017 of J. Almeida are all acknowledged